Respostas

2013-05-28T18:53:51-03:00

Olá!!!!

 

3x² -4x -2 = 0      neste caso temos que fazer por bháskara!!...a resolução está em anexo!!

 

4 4 4
2013-05-28T19:12:34-03:00

3x²-4x-2=0

 

Δ= (-4)²-4*3*(-2)

Δ=16+24

Δ=40

 

x=-(-4)±√404±√2²*2*5 =4±2√10

      2*3             6                         6

 

x'=4+2√10--------------2+√10

           6                            3

x"= 4-2√10-------------2-√10

            6                          3

 

S={ 2+√10 , 2-√10  }

     {      3             3    }

 

2 3 2